2013
DOI: 10.1007/s00420-013-0894-5
|View full text |Cite
|
Sign up to set email alerts
|

Incidence rates of surgically treated rhegmatogenous retinal detachment among manual workers, non-manual workers and housewives in Tuscany, Italy

Abstract: PurposeCandidate risk factors for idiopathic rhegmatogenous retinal detachment (RRD) include heavy manual handling (requiring Valsalva’s maneuver). We assessed incidence rates of surgically treated idiopathic RRD among manual workers, non-manual workers and housewives resident in Tuscany, Italy.MethodsWe retrieved all hospital discharge records bearing a principal diagnosis corresponding to RRD coupled with retinal surgery for any resident of Tuscany during 1997–2009. After elimination of repeated admissions a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
2

Year Published

2015
2015
2020
2020

Publication Types

Select...
5

Relationship

5
0

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 21 publications
0
9
2
Order By: Relevance
“…Mattioli and colleagues also reported a six-fold increase in risk of RRD among subjects with a BMI≥25.5 kg/m 2 or more compared with those with a BMI between 21 and 23 kg/m 2 7. Our estimates are lower and we did not observe an increased hazard of RRD among overweight subjects.…”
Section: Discussioncontrasting
confidence: 65%
“…Mattioli and colleagues also reported a six-fold increase in risk of RRD among subjects with a BMI≥25.5 kg/m 2 or more compared with those with a BMI between 21 and 23 kg/m 2 7. Our estimates are lower and we did not observe an increased hazard of RRD among overweight subjects.…”
Section: Discussioncontrasting
confidence: 65%
“…As a preliminary descriptive analysis, and for comparison with the previous Danish Cohort Study,8 we calculated the IRs of RRD by broad occupational class (manual and non-manual workers) (table 2). In crude analyses, manual workers (who presumably perform more heavy lifting) had lower rates of RRD than non-manual workers which contradicts our hypothesis but is consistent with the Danish study.…”
Section: Resultsmentioning
confidence: 99%
“…However, the Scottish Study analysed ecological data, did not include individual information on occupation (the only available data was the percentage of unemployed in the area) and crucially did not have information on myopia. An Italian register-based study of surgically treated RRD showed higher age SIRs among manual workers compared with non-manual workers 8. The authors hypothesised that occupational lifting might have contributed to explain the observed difference.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…The study population and the data collection were described in detail elsewhere ( Mattioli et al , 2009b ; Curti et al , 2014 ). Briefly, information on 17988 surgically treated cases of CTS among residents of Tuscany occurring during 1997–2000 was collected from obligatory discharge records of all Italian public/private hospitals.…”
Section: Methodsmentioning
confidence: 99%